Evaluation of the Relationship Between Foreign Patients\' Satisfaction and Financial Dimension, Treatment Quality, and Treatment and Tourism Facilities in Hospitals of Iran University of Medical Sciences - Fatemeh Najafipour Moghadam; Nader Tavakoli; Khadijeh Nemati; Narges Pak (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Medical tourism provides Effective economic, political and social profits to the countries active in the field, which should be taken into account in a competitive market. This study aimed to evaluate the relationship between foreign patients' satisfaction and other aspects of health tourism in educational and medical centers of the Iran University of Medical Sciences (IUMS). Methods: This was a descriptive correlational study with a researcher-made questionnaire. The first part of the questionnaire contained the demographic characteristics of the participants, and the second part included 30 questions about the components that affect receiving medical services by foreign nations. The reliability coefficient of the questionnaire was determined by using Cronbach's alpha (0.980). Expert judgment was used to assess the validity of the questionnaire. Out of 70 hospitals affiliated with the University of Iran in 2019, 10 hospitals from 35 licensed centers in the field of international health were randomly selected, and 300 questionnaires were delivered to foreign patients who were willing to complete the questionnaire. The received information was from Random sampling recorded in SPSS25 software. Descriptive Statistics was used to determine the effective factors.   Results: The largest numbers of foreign patients in this study were from Iraq (64 %) and Kuwait (24 %), respectively. In correlation review, there was a significant relationship between satisfaction of foreign patients and financial dimension (0.785), quality of treatment dimension (0.914), medical facilities dimension (0.799) and tourism facilities dimension (0.918) in hospitals. Conclusion: This study demonstrates that there is a significant relationship between satisfaction of foreign patients and other aspects of health tourism (such as financial dimension, treatment quality, treatment and tourism facilities) in hospitals, Which needs to be given special attention by health tourism managers for short-term and long-term planning for its development.